Inside Front Cover: Helical Structure Endows Liquid Crystal Planar Optics with a Customizable Working Band (Adv. Quantum Technol. 2/2023). Issue 2 (9th February 2023) - Chen, Quan‐Ming; Xu, Chun‐Ting; Liang, Xiao; Hu, Wei
Abstract : Multi‐degree orthogonal manipulation of light, especially the on‐demand tailoring of the working band and spatial phase front, is expected to fully exhibit the superiority of photons as information carriers. In article number 2200153 by Xiao Liang, Wei Hu, and co‐workers, recent progresses on helical liquid crystal planar optics with customizable working band are reviewed. The new elements will boost the capability of information transporting and data processing.